If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9l + -20 = 86 Reorder the terms: -20 + 9l = 86 Solving -20 + 9l = 86 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '20' to each side of the equation. -20 + 20 + 9l = 86 + 20 Combine like terms: -20 + 20 = 0 0 + 9l = 86 + 20 9l = 86 + 20 Combine like terms: 86 + 20 = 106 9l = 106 Divide each side by '9'. l = 11.77777778 Simplifying l = 11.77777778
| 20-9l=86 | | 3byx(-5yb)= | | 16=m-6 | | (2x+10)(x-12)= | | 2x+2*4=16 | | (3-2i)(x+iy)=2(x-2iy)+2i-1 | | 3x/5+44=12x/25+8 | | 2x-3*4=-4 | | -149-7x= | | 4w+10=96 | | 3x/8-9=13+x/8 | | y/5.4=7.2 | | 2t^2+4t+8=0 | | -2y+7=Y | | 96/10 | | b/-8=23 | | 3x-14=2xd+10 | | 3.2x=6.8 | | 4w=102 | | x/9=135 | | 123+a=201 | | x-143=16 | | -7x=-133 | | 4w=90 | | 3x-10x=8x-30 | | y^2-6y-14=0 | | x^2+0.3x-0.1=0 | | 196=-14y | | -5*7+42/6 | | X^2-3x+2=2 | | 50x-13=55x-93 | | 3x^2+9x+1=0 |